Iron corrosion by methanogenic archaea characterized by stable isotope effects and crust mineralogy. (14th July 2021) - Tamisier, Marc; Schmidt, Matthias; Vogt, Carsten; Kümmel, Steffen; Stryhanyuk, Hryhoriy; Musat, Niculina; Richnow, Hans‐Hermann; Musat, Florin
Summary: Carbon and hydrogen stable isotope effects associated with methane formation by the corrosive archaeon Methanobacterium strain IM1 were determined during growth with hydrogen and iron. Isotope analyses were complemented by structural, elemental and molecular composition analyses of corrosion crusts. During growth with H2, strain IM1 formed methane with average δ 13 C of −43.5‰ and δ 2 H of −370‰. Corrosive growth led to methane more depleted in 13 C, with average δ 13 C ranging from −56‰ to −64‰ during the early and the late growth phase respectively. The corresponding δ 2 H were less impacted by the growth phase, with average values ranging from −316 to −329‰. The stable isotope fractionation factors, α 13 C CO 2 / CH 4, were 1.026 and 1.042 for hydrogenotrophic and corrosive growth respectively. Corrosion crusts formed by strain IM1 have a domed structure, appeared electrically conductive and were composed of siderite, calcite and iron sulfide, the latter formed by precipitation of sulfide (from culture medium) with ferrous iron generated during corrosion. Strain IM1 cells were found attached to crust surfaces and encrusted deep inside crust domes. Our results may assist to diagnose methanogens‐induced corrosion in the field and suggest that intrusion of sulfide in anoxic settings may stimulate corrosion by methanogenic archaea via formation of semiconductive crusts.